Bilateral Investment Treaties and the Increase in Egyptian Appearances Before International Arbitration Tribunals - Elfakharani, Ashraf M. A.; Abdul Rahman, Rohana; Albaheth, Hamza E.; Abdullah, Nor Anita (Edinburgh University Press, 2021)
A bilateral investment is a written accord between any two nations holding diverse positions but having intentions to hold investment relations between themselves. Bilateral investment treaties (BITs) are thus agreements which monitor investment relations between any two signatory states to safeguard their interests in terms of overseas investments by providing safety to all their foreign investors